2022
DOI: 10.1080/02614367.2022.2131888
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the importance of sport stadium visits to teams and cities through the eyes of online reviewers

Abstract: This study explores the relationships among sport stadium visitors' experiences, satisfaction, team brand image, and destination image. A text mining approach was first used to analyse 26,538 individual reviews from 17 European sport stadiums on TripAdvisor. The online reviews were then used as input to create a word frequency of each individual review and construct a structural equation model. Results indicate that the visitor experience had a strong impact on team brand image and a moderate effect on destina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…When the indicator’s outer loading is less than 0.50 but significant, its removal should be considered. However, removing the indicator requires careful analysis, as its elimination may omit unique parts of the variable’s composition, thus reducing its theoretical validity (Ramos et al , 2023). Following these recommendations, the Empathy indicator was removed (outer loading = 0.103; p- value = 0.082).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the indicator’s outer loading is less than 0.50 but significant, its removal should be considered. However, removing the indicator requires careful analysis, as its elimination may omit unique parts of the variable’s composition, thus reducing its theoretical validity (Ramos et al , 2023). Following these recommendations, the Empathy indicator was removed (outer loading = 0.103; p- value = 0.082).…”
Section: Resultsmentioning
confidence: 99%
“…Reviews that do not follow the standard pagination format may not have been captured due to using a web scrapper. Although a panel of experts validated the dictionary, this process will always contain inherent subjectivity (Ramos et al , 2023), influencing final results. The accuracy and authenticity of TripAdvisor’s online reviews could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using PLS-SEM, marketing researchers can explore complex relationships among variables, test research hypotheses, identify the relative importance of different influencers and assess the validity and reliability of the measured variables (Sarstedt et al, 2019). It is frequently used in research involving the modeling of theoretical constructs, such as customer satisfaction (Ramos et al, 2022), brand image (Kunkel et al, 2020) or perceived quality (Ariffin et al, 2021) research. Surprisingly, there are no articles from 2018 in the top 10 most cited articles.…”
Section: Most Influential Articlesmentioning
confidence: 99%